2021
DOI: 10.2147/jir.s344990
|View full text |Cite
|
Sign up to set email alerts
|

Isosteviol Sodium Exerts Anti-Colitic Effects on BALB/c Mice with Dextran Sodium Sulfate-Induced Colitis Through Metabolic Reprogramming and Immune Response Modulation

Abstract: Purpose: Inflammatory bowel diseases (IBDs) are global health problems that are associated with immune regulation, but clinical IBDs treatment is currently inadequate. Effective preventive or therapeutic methods for immune disorders rely on controlling the function of immune cells. Isosteviol sodium (STV-Na) has antioxidant activity, but the therapeutic effect of STV-Na against IBD remain undocumented. Herein, we investigated the therapeutic effect of STV-Na in mice models with IBDs. Methods: Mice received 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Previous immunotherapeutic treatments for IBD have focused on reducing M1 macrophages and increasing M2 macrophages to reduce the damage caused by pro-inflammatory factors secreted by M1 macrophages in the intestine [113]. However, M2-related genes have a greater role than simply suppressing inflammation, and subsequent adverse manifestations, such as fibrosis and granulomas, suggest that simply switching between M1 and M2 phenotypes is not a beneficial therapeutic approach [22,71]. Instead, sustaining a well-balanced ratio of polarized phenotypes or finding a solution to increase the number of anti-inflammatory phenotypic macrophages while mitigating the side effects associated with conventional therapies should be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous immunotherapeutic treatments for IBD have focused on reducing M1 macrophages and increasing M2 macrophages to reduce the damage caused by pro-inflammatory factors secreted by M1 macrophages in the intestine [113]. However, M2-related genes have a greater role than simply suppressing inflammation, and subsequent adverse manifestations, such as fibrosis and granulomas, suggest that simply switching between M1 and M2 phenotypes is not a beneficial therapeutic approach [22,71]. Instead, sustaining a well-balanced ratio of polarized phenotypes or finding a solution to increase the number of anti-inflammatory phenotypic macrophages while mitigating the side effects associated with conventional therapies should be the focus of future research.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate if metabolism determines the macrophage phenotypes or whether macrophage polarization phenotypes determine metabolic status, numerous efforts have been made to determine the causal relationship between the two by demonstrating that alterations in specific cellular metabolism affect the macrophage phenotype and modulate the cytokine secretion profile at the level of bone marrow-derived macrophages [70]. The metabolic properties of M1 and M2 macrophages differ, and aerobic glycolysis is involved in macrophage M1 polarization, oxidative phosphorylation is involved in macrophage M2 polarization, and changes in metabolism have different effects on diverse macrophage phenotypes, which are reflected by a strong effect on the phenotype of M1 macrophages [70][71][72]. In IBD, Lee et al [73] found that LMT503 was able to alleviate IBD by promoting macrophage reprogramming.…”
Section: Macrophage Polarization and Metabolismmentioning
confidence: 99%
“…To investigate the ameliorative effect of IPA on colitis inflammation in mice, we established a DSS- induced acute colitis murine model. Weight loss, shortened colonic length, and increased colonic weight are commonly used as indicators of the severity of IBD ( 36 ). IBDs are characterized by body weight loss, bloody feces, diarrhea, shortening of the colon length, and splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages highly express TNF-α, which is associated with inflammation. [37] An immunohistochemical analysis of liver tissue using F4/80 (a marker of macrophages including M0) and CD86 (a marker of M1 macrophages) [37] demonstrated that BDL significantly increased both M0 and M1 macrophages in the liver on cholestatic mice on POD-14 (Fig. 5E, F).…”
Section: Nets Exacerbate the Inflammatory Load In Cholestatic Mice An...mentioning
confidence: 98%